Political Power in Trump's Speech of Coronavirus Outbreak: A Pragmatics Study of Illocutionary Acts - Rizky Dea Safitri; Lina Purwaning Hartanti (Politeknik Negeri Padang, 2021)
This study attempts to find the purpose behind Trump's political speech by using the theory of the illocutionary act by Searle and the power dimension theory by Lukes. The data of this study is one of Donald Trump's speeches titled TRUMP AND CORONAVIRUS TASK FORCE HOLD WHITE HOUSE BRIEFING, uploaded by NBC News Youtube Channel on April 19, 2020. A qualitative method is required to gain the objective and specific result. The result shows that Trump uses assertive, commissive, expressive, and directive illocutionary speech consist of ideological power or manipulation that reveal some purposes behind Trump's political speech. The ideological power used in Trump's speech in manipulating and persuasion can influence and shape people's perception. As president of the US, his utterances aim to show the greatness of the country he leads in handling a pandemic outbreak. Also, some of Trump's utterances express aversion towards China because of the trade war and the COVID-19 virus that infected his people. Moreover, one of his utterances purposes of manipulating Iran to deal with the nuclear program. Also, Trump's utterance used to direct American to choose him in the coming presidential election.